Facile in situ Electrosynthesis and High Electrocatalytic Performance of Interconnected Layered Double Hydroxides/Graphene Hybrids for Dopamine Oxidation: A Comparative Study. Issue 3 (7th December 2018) - Kumar, M. Kaleesh; Swaathini, K. C.; Jha, Niki S.; Jha, Shailendra K.
Abstract: We are reporting a facile in situ electrodeposition approach to prepare a rational design of M−Al (M: Ni, Co) layered double hydroxide (LDH)/reduced graphene oxide (G) hybrids and its superior electrocatalytic activity towards the electrooxidation of dopamine. Comparatively, the worm like interconnected nano‐chain networks of as‐prepared NiAl‐LDH/G hybrid modified electrode exhibits better performance than the CoAl‐LDH/G hybrid modified electrode. The enhanced electrocatalytic activity is because of its morphological evolution, which is due to its enhanced reduction rate, attachment pathway and incorporation or heterogeneous combination of Al 3+ in the bimetallic LDHs/G hybrid. The satisfactory results are obtained for modified electrodes for the real‐time quantitative detection of dopamine in the real injectable medicine as well as human blood serum samples and it has also shown good reproducibility, stability and anti‐interference. This cost‐effective and facile in situ electrodeposition approach will give insights to design high performing hybrid materials and its application to non‐invasive electrochemical sensing which will be useful for daily diagnosis of neurological disorder. Abstract :